Vascular calcification - is aldosterone a culprit? - Lang, Florian; Ritz, Eberhard; Voelkl, Jakob; Alesutan, Ioana (Nephrology, dialysis, transplantation, 2013)
In chronic kidney disease (CKD), increased plasma phosphate concentrations cause vascular calcification which substantially contribute to cardiovascular events and increased mortality of CKD patients. Similar to CKD patients, klotho-hypomorphic mice (kl/kl) also suffer from excessive vascular calcification leading to growth deficit, rapid ageing and early death. The hyperphosphataemia of kl/kl mice results from excessive formation of 1,25(OH)2D3 causing excessive intestinal phosphate absorption. Further, kl/kl mice further suffer from hyperaldosteronism and compelling evidence points to an active role of mineralocorticoids in triggering osteoinductive programmes in the vasculature, thus further contributing to the development of vascular calcification. Conversely, in kl/kl mice, the mineralocorticoid receptor antagonist spironolactone decreased the vascular osteoinductive processes and reversed the excessive expression of osteogenic programmes, i.e. type III sodium-dependent phosphate transporter Pit1, tumour necrosis factor α (Tnfα), transcription factors Msx2, Cbfa1/Runx2 and osterix as well as alkaline phosphatase (Alp). In human aortic vascular smooth muscle cells (HAoSMCs), aldosterone alone similarly triggered an ‘osteogenic’ programme, thus increasing PIT1, TNFα, MSX2, CBFA1/RUNX2 and ALP expression as well as ALP activity and potentiated the effects of phosphate treatment. These effects were again reversed by spironolactone and in addition by PIT1 silencing. The above observations reveal that the severe vascular calcification is not only the result of high plasma phosphate concentrations, but also promoted by aldosterone-driven osteoinductive signalling. Future studies in CKD patients will be required to define the role of aldosterone and the potential impact of its inhibition by spironolactone in the pathophysiology of vascular calcification.